2014
DOI: 10.1108/ijse-12-2012-0232
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and economic growth in GCC countries

Abstract: Purpose – The purpose of this paper is to compare the effects of Islamic financial development and conventional financial development on the economic growth for five GCC countries (Bahrain, Kuwait, Qatar Saudi Arabia and UAE). Design/methodology/approach – Using generalized least squares, OLS and panel data frameworks, this paper employs different measures of financial development for the period (1996-2011). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…Ageli and Zaidan (2013) found that credit provided by government specialized bank and commercial banks to private sector has a positive effect on GDP using vector error correction model (VECM). Grassa and Gazdar (2014) examined the impact of total finance, conventional finance, and Islamic finance on economic growth as proxied by the growth rate of real per capita GDP in Gulf Cooperation Council (GCC) countries, excluding Oman. The author found that total domestic credit to private sector as a percentage of GDP is not significant using OLS, Panel estimators (fixed effect and random effect), and GLS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ageli and Zaidan (2013) found that credit provided by government specialized bank and commercial banks to private sector has a positive effect on GDP using vector error correction model (VECM). Grassa and Gazdar (2014) examined the impact of total finance, conventional finance, and Islamic finance on economic growth as proxied by the growth rate of real per capita GDP in Gulf Cooperation Council (GCC) countries, excluding Oman. The author found that total domestic credit to private sector as a percentage of GDP is not significant using OLS, Panel estimators (fixed effect and random effect), and GLS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Bhattacharyya and Hodler (2014) argued that if the political-institutional quality is poor, so the result reported with statistical evidence that found a negative association. In China, Yuxiang and Chen (2011) In the case of GCC panel countries, Grassa and Gazdar (2014) by employing OLS, and GLS approaches, and result indicates the negative and significant impact of financial development on economic growth. In contrast, Bist (2018) analyzed the association of financial development on economic growth in the long run by employing the OLS approach over using panel data of 20 years.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Patrick (1966) proposed the stages of development model, of financial development influencing economic growth at the primary stage of economic expansion and declines as the economy expands for economic growth to influence financial stability. Kar, Nazlıoğlu, and Ağır (2011) in the Middle East and North Africa (MENA) countries and Grassa and Gazdar (2014) in the Gulf Cooperation Council (GCC) observed neutrality. Financial and economic data support the Casino Neutrality of a non-significant relationship.…”
Section: Literature Reviewmentioning
confidence: 99%